Modulation of the Gut Microbiota by Fufang-Zhenzhu-Tiaozhi Capsule Attenuates Hypertension Induced by a High-Fructose and High-Salt Diet - Chen, Zhe; Yang, Bin; Wang, Zhen; Rong, Xianglu; Zhu, Qing; Guo, Jiao (Frontiers in Cellular and Infection Microbiology, 2022)
Hypertension is frequently comorbid with the disorders of glucose and lipid metabolism. The increased intakes of fructose and salt contribute to the development of hypertension and related metabolic disorders, which are closely associated with gut dysbiosis. Fufang Zhenzhu Tiaozhi capsule (FTZ), a traditional Chinese patent medicine commonly used in clinical practice, has recently emerged as a promising drug candidate for metabolic diseases. In this study, FTZ treatment is identified as attenuating blood pressure increase and improving the metabolism of lipid and uric acid in high-fructose and high-salt (HFS) diet-fed rats. FTZ also substantially alleviated renal fibrosis and the mRNA expression of inflammation cytokines, NADPH oxidases, and renin-angiotensin system in the renal cortex. 16S rRNA sequencing of fecal samples revealed that FTZ restored HFS-induced gut dysbiosis, seen the increased intestinal microbial richness and diversity. Furthermore, fecal microbiota transplantation also achieved similar therapeutic effects and alterations in gut microbiota profile induced by FTZ. Taken together, this study highlights the efficacy of FTZ in attenuating HFS-induced hypertension and related metabolic disorders and renal injury. The antihypertensive effect is associated with the modulation of gut microbiota.